Systematic Review of Matrix Training for Individuals With Autism Spectrum Disorder. (March 2020) - Curiel, Emily S. L.; Axe, Judah B.; Sainato, Diane M.; Goldstein, Howard
Matrix training is an intervention that systematically programs for the occurrence of generative outcomes, mostly in the area of language. A literature search identified studies that evaluated matrix training with individuals with autism spectrum disorder (ASD). Based on 12 reviewed studies, we asked questions regarding participant characteristics, targeted skills, matrix designs, evidence-based teaching strategies, percentage of learning that occurred through direct teaching and recombinative generalization, and the quality of the studies. With 29 total participants, mostly preschool and elementary ages, the most common teaching strategy implemented was a discrete trial training paradigm targeting language development. Overall, findings suggest that matrix training produced an average of 69% of learning without direct teaching across the areas of language, play, sentence construction, and spelling.